Growth Hormone (GH) Improvement of Ovarian Responses and Pregnancy Outcome in Poor Ovarian Responders: A Randomized Study - Safdarian, Leyli (Asian Pac J Cancer Prev, 2019)
Recent evidence has emphasized growth hormone benefits in increasing the ovarian response and improving the pregnancy rate in poor responders (POR), caused by aging, ovarian surgery, chemotherapy and other reasons, undergoing IVF/ICSI. The most important factor in the treatment of POR patients is the quality and quantity of oocytes following ovarian stimulation; thus, efforts should be made to provide opportunities for young patients to improve their fertility and ovarian responses. The use of GH in these patients may offer a promising aid to successful fertility.In the present single-blinded clinical trial, POR patients were randomly assigned to receive one of three regimens: (A) Gonadotropin, a GnRH antagonist and GH from the eighth day of the cycle for about 5 days (n = 34); (B) Gonadotropin, a GnRH antagonist and GH from the third day of the previous cycle for about 20 days (n = 32); and (C) Gonadotropin, a GnRH antagonist, and a placebo from the eight day of the cycle for about 5 days (n = 26). Oocyte quality and pregnancy rates were compared across the three groups. A significantly lower number of collected oocytes, MII oocytes, fertilized oocytes, transferred embryos, and clinical pregnancy rate in the placebo group was noted as compared to the two experimental groups receiving GH. Live clinical pregnancies in B group were significantly greater than in the other groups. Our results together indicate that GH may play an important role in recruitment of dominant follicles and enhance follicular survival and the cell proliferation leading to high- quality embryos. Accordingly, administration of GH can considerably elevate the ovarian response in patients with POR planned to undergo IVF.